Silicon-based Photonic Integrated Circuits for the Mid-infrared. (2016) - Malik, Aditya; Muneeb, Muhammad; Radosavljevic, Sanja; Nedeljkovic, Milos; Penades, Jordi Soler; Mashanovich, Goran; Shimura, Yosuke; Lepage, Guy; Verheyen, Peter; Vanherle, Wendy; Van Opstal, Tinneke; Loo, Roger; et al.
Abstract: Silicon-based photonic integrated circuits (PICs) operating in the mid-infrared wavelength range are presented. Firstly, it is shown that the operation of the SOI-based waveguide circuits can be pushed beyond the telecom window till a wavelength of 4 μm. Ge-on-Si based PICs are demonstrated for operation beyond 4 μm wavelength. Low-loss waveguides and integrated spectrometers are reported for both the waveguide platforms. We also present our results on efficient thermo-optic phase shifters for germanium waveguide circuits.